RESPON PERTUMBUHAN DAN HASIL TANAMAN SEMANGKA (Citrullus vulgaris Schard) AKIBAT PEMBERIAN POC LIMBAH BUAH BUAHAN DI TANAH GAMBUT: Plant Growth and Yield Response Watermelon (Citrullus vulgaris Schard) due to Application of Liquid Organic Fertilizer of Fruit Waste on Peat Soils - Sando Johnwick Sibuea; Hastin Ernawati Nur Chusnul Chotimah; Susi Kresnatita; Oesin Oemar; Ahmat Sajarwan (Fakultas Pertanian Universitas Palangka Raya, 2022)
This study aims to determine the best interaction between watermelon varieties and the application of liquid organic fertilizer from fruit waste, the best dose, and the suitable varieties for cultivation on peat soils. The design used was a 4 x 2 factorial RCBD (Randomized Completely Block Design) with 3 replications. The factors studied arethe variety (V) consists of two levels, namely: V1: Amara F1, V2: Garnis F1, and liquid organic fertilizer (P), consists of four levels, namely: P0: 0/liter of water, P1: 30 mL +970 mL of water/plot, P2: 60 mL+940 mL of water/plot, P3: 90 mL+910 mL of water/plot. The results showed that there was no interaction between varieties and liquid organic fertilizers. The varieties had a significant effect on plant length, the number of leaves, flowering time, and fruit length. The suitable variety was Garnis F1. The liquid organic fertilizers had a significant effect on fruit weight per plot, and fruit diameter with the best dose of 30 mL+970 mL of water/plot on the Garnis F1 variety. The highest fruit sweetness rate (7.72 Brix) at the best dose 90 mL+910 mL of water/plot on the Garnis F1 variety